Physical Activity as a Non-Pharmacological Intervention for Chronic Pain in Elderly Gouty Arthritis - Siti Naimatuz Zahro; Dina Camelia; Leo Yosdimyati R; Tiara Fatma P (International Journal of Health Engineering and Technology, 2026)
Chronic pain in elderly people with gout arthritis remains a problem that lacks structured treatment, negatively impacting their quality of life and daily activities. This study aims to analyze the effect of physical activity on the level of chronic pain in elderly people with gout arthritis in Kejambon Hamlet, Dapurkejambon Village. The study used a quantitative research type with a pre-experimental one group pretest-posttest design. The study was conducted on elderly people experiencing gout arthritis pain with a mild and moderate pain scale, taken using a purposive sampling technique according to the inclusion and exclusion criteria, resulting in 20 respondents. Data were collected using a pre-post test pain scale observation sheet and analyzed using the Wilcoxon Signed Ranks Test. The results showed that, before the intervention, most respondents experienced moderate pain (15 respondents (75%), and after the intervention, most respondents experienced a decrease in pain levels to mild (15 respondents (75%). The Wilcoxon test results showed a significance value of 0.001 (p <0.05), which means there is a significant effect of physical activity on reducing the level of chronic pain in elderly people with gout arthritis. It was concluded that physical activity significantly reduced chronic pain levels in elderly people with gouty arthritis. This study recommends that this activity can be used as an effective non-pharmacological intervention in geriatric nursing practice.